Key Factors Influence the Expenditure of Breast Milk in Post-Sectio Cesareana Mothers at Regional Hospital Batam, Indonesia - Novitasari, Jennie; Nadapdap, Thomson; Nasution, Ramadhani Syafitri (Hasanuddin Medan, 2024)
Aim and objective of this research is to establish the relating and contributory factors to the formation of breast milk among post-caesarean section (SC) mothers at Embung Fatimah Regional Hospital Batam City. Breastfeeding is known to offer lots of health benefits to the baby, and the mother as well; unfortunately, many post-SC mothers face difficulties in lactation. Sequential exploratory design was used: quantitative data was collected from 54 post-SC mothers, qualitative data from post-SC mothers, midwives and health staff. Some of the factors that were examined in the study included; frequency of feedings, breast care, rooming-in, maternal diet, birth weight, feeding techniques employed and the gestational period. Altogether, quantitative findings pointed towards the association of independent variables with smooth breast milk production as follows: regularly frequency of breastfeeding (p = 0. 000), proper care of the breasts (p = 0. 002), rooming in (p = 0. 002), adequate diet of the mothers (p = 0. 000), mothers’ gestational age /full term/b (p = 0. Other observable variables such as mode of feeding which includes the combined nursing care and birth weight do not significantly predict each other. Most dominant factors considered by the logistic regression analysis were maternal nutrition and the frequency of breastfeeding. The qualitative results that supported the significance of educating women on how to breast feed, proper care of the breast and the value of family support on breastfeeding results. There was also an indication that mothers who were closely monitored by midwives and other health care givers experienced less problems in their milk flow. These results emphasise the need to enhance the provisions of breastfeeding education, healthcare and nutrition; especially for post-SC mothers to ease successful breastfeeding and improve the health of both mother and child.